Videojogos 2019: 11th International Conference on Videogames Sciences and Arts: book of abstracts - Ribeiro, Tânia (2019)
Videojogos is an annual conference on videogame sciences and arts, promoted by the Portuguese Society of Video Games Sciences (SPCV). Since its first edition, in 2009, the conference has been promoting the scientific gathering of researchers and professionals in the expanded field of videogames. As in the first edition, Aveiro once again holds the conference. The 11th Conference on Videogame Sciences and Arts – Videojogos 2019 takes place in the University of Aveiro, Portugal, during November 27-29. The event is co-organized by the Department of Communication and Art of the University of Aveiro (DeCA), DeCA’s DigiMedia Research Center and the Portuguese Society of Video Games Sciences (SPCV). This year, 10 years after the first conference, SPCV and the co-organizers decided to convert the conference into a full international event, with English as a working language. As one of the outcomes of this decision, the proceedings of Videojogos 2019 will be published by Springer in their “Communications in Computer and Information Science” (CCIS) book series, part of a post-conference volume with the number 1164. This Book of Abstracts is more than a shortened version of the proceedings. Besides abstracts from the 20 selected papers that will be published in the book series, it contains abstracts from the research posters (8) and videogame demos (9) accepted for the conference, as well synopsis for other activities held at the conference such as keynotes (2) and workshops (3). Thanks to UA Editora, we were able to present this book in time for the conference, providing an overview into the diversity of contributions gathered in the videogame context. We would like to thank the scientific board for their contribution to guarantee and deliver the highest scientific quality, allowing the outstanding relevance of this selection. We also would like to thank the program chairs (demo, poster and workshops) and the organization team for all their concerns and efforts in the organization, an extremely important contribution for the overall success of the Videojogos 2019 Conference. Finally, a note of appreciation to the American Corner of the University of Aveiro, which provided essential logistical support, namely by ensuring the presence of Professor Ernest Adams as Keynote Speaker and to the University of Aveiro publisher, UA Editora, for their support and collaboration in this publication.